Potensi Usaha Rumahan Di Desa Balaroa Pewunu Kecamatan Dolo Barat Kabupaten Sigi - Ilham. S; Mohammad Zeylo Auriza; Harnida Wahyuni Adda (Sammajiva: Jurnal Penelitian Bisnis dan Manajemen, 2023)
Balaroa Pewunu Village has home-based businesses, namely banana chips, brown sugar chips, biapong cakes and pop ice. Home business is one of the efforts to meet household economic needs. A home-based business in running its business certainly requires good management, so that the business can continue to run. However, home businesses have not managed home businesses well. Community Service activities carried out are focused on managing home-based businesses. The purpose of this article is to serve so that it helps in managing home businesses, especially financial management, innovating products and expanding market share. The implementation method is carried out through observation, training and mentoring. The results achieved from this implementation are that home-based businesses have implemented simple bookkeeping records such as making cash flow books, inventory books, product sales books and production cost books.